Spatial distribution of D1R- and D2R-expressing medium-sized spiny neurons differs along the rostro-caudal axis of the mouse dorsal striatum - Gangarossa, Giuseppe; Espallergues, Julie; Mailly, Philippe; De Bundel, Dimitri; De Kerchove D'Exaerde, Alban; Hervé, Denis; Girault, Jean-Antoine; Valjent, Emmanuel; Krieger, Patrik (Frontiers in Neural Circuits, 2013)
The striatum projection neurons are striatonigral and striatopallidal medium-sized spiny neurons (MSNs) that preferentially express D1 (D1R) and D2 (D2R) dopamine receptors, respectively. It is generally assumed that these neurons are physically intermingled, without cytoarchitectural organization although this has not been tested. To address this question we used BAC transgenic mice expressing enhanced green fluorescence (EGFP) under the control of Drd1a or Drd2 promoter and spatial point pattern statistics. We demonstrate that D1R- and D2R-expressing MSNs are randomly distributed in most of the dorsal striatum, whereas a specific region in the caudal striatum, adjacent to the GPe, lacks neurons expressing markers for indirect pathway neurons. This area comprises almost exclusively D1R-expressing MSNs. These neurons receive excitatory inputs from the primary auditory cortex and the medial geniculate thalamic nucleus and a rich dopamine innervation. This area contains cholinergic and GABAergic interneurons but apparently no D2R/A2aR modulation because no fluorescence was detected in the neuropil of Drd2-EGFP or Drd2-Cre, and Adora-Cre BAC transgenic mice crossed with reporter mice. This striatal area that expresses calbindin D28k, VGluT1 and 2, is poor in μ opiate receptors and preproenkephalin. Altogether, the differences observed in D1R-MSNs, D2R-MSNs, and interneurons densities, as well as the anatomical segregation of D1R- and D2R/A2aR-expressing MSNs suggest that there are regional differences in the organization of the striatum.